Community-Based Agritourism: A Qualitative Research of the Impacts, Opportunities, and Constraints in a Tourist Village - SAEPUDIN, Pudin; PUTRA, Fajar Kusnadi Kusumah; HERNOWO, Andre; MAEMUNAH, Ita; DIANAWATI, Nenden (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022, 2022)
This research aims to determine the motivation for the community-based agritourism activities in the tourist village. This research was conducted qualitatively using structured in-depth interviews with twelve key participants, which include the tourist village managers, village heads, farmers, culinary and agricultural product entrepreneurs, and tour guides. The findings showed six dimensions of community-based agritourism which are economic impact, environmental conservation, learning activities, sociocultural preservation, stakeholder participation, and marketing promotion. Some obstacles found for the implementation of community-based agritourism include changes in mindset and lifestyle, inequality of opportunity, and lack of professional staff to conduct tourism activities. According to the participants there are several aspects need to be improved, including local tourism management, financial support, development of tourism-supporting infrastructure, and training for communities involved in tourism activities. This study found that agritourism has economic benefits for local stakeholders, encourage nature conservation, and encourage more local community participation. The Agritourism activities has strengthen the local community in managing tourism using their daily main activity which is farming. This research has limitations from the perspective of the external environment of the tourist villages, such as the government, tourists and residents, and tourism business partners. Therefore, further research can be conducted by taking the opinions of the government representatives, tourists, residents, and tourism business partners.